ANALYSIS OF PUBLIC SERVICE PERFORMANCE IN THE FIELD OF POPULATION ADMINSTRATION IN TAKERAN DISTRICT, MAGETAN REGENCY: ANALISIS KINERJA PELAYANAN PUBLIK BIDANG ADMINISTRASI KEPENDUDUKAN DI KECAMATAN TAKERAN KABUPATEN MAGETAN - Muhammad Wahyu Afandi; Harianto; Bambang Martin Baru (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Public services are the main issue because of the lack of efficiency and effectiveness in their implementation, even though it is an important aspect as a bridge between the government and the community. The public can assess the government's performance from the quality of public services, which is the most visible benchmark for government performance. Improving public services focuses on convenience, speed, transparency, and shortening bureaucracy. This study aims to analyze the performance of public services in Takeran District, focusing on performance quality, quantity, timeliness, effectiveness, and independence. This study uses a descriptive qualitative approach with observation, interview, and documentation methods. The results of the study are expected to provide an overview of the performance of public services in the field of population administration in Takeran District